User Generated Content (UGC) to Visit and Purchase Intention: Literature Review - Christine, Christine; Syafrizal Helmi Situmorang; Beby Karina Fawzeea Sembiring (Forum Kerjasama Pendidikan Tinggi, 2024)
Traditional communication and marketing methods are no longer adequate in the digital age, where variousplatforms have emerged, allowing easy access to interconnected information and products. The presence ofnew media, facilitated by technology and the internet, has changed the way individuals and groups interactglobally. Social media, one of the leading media platforms, allows users to share data, photos, and videos; asa result, user generated content (UGC) has emerged. The methodology applied in this article is a systematicliterature review using academic journals and conference proceedings. The purpose of this literature review isto gain a broad understanding of UGC. The findings of this review highlight the positive relationship betweenUGC and visit intention such as in travel accommodation choices, particularly in booking eco-friendlylodging and product purchase intention.